2000
DOI: 10.1016/s0735-1097(00)00735-x
|View full text |Cite
|
Sign up to set email alerts
|

Regional diastolic function by pulsed doppler myocardial mapping for the detection of left ventricular ischemia during pharmacologic stress testing

Abstract: Quantification of diastolic myocardial function by pulsed Doppler myocardial mapping during dobutamine stress test was shown to be a feasible, accurate, reproducible, noninvasive technique that should be considered to be a sensitive alternative to the present echocardiographic and scintigraphic imaging techniques for stress tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 31 publications
4
61
0
5
Order By: Relevance
“…Regarding late diastolic velocity (A), there was no significant difference between the two groups. These results are in agreement with data reported by Von Bibra et al [37] using pulsed Doppler myocardial mapping of 12 left ventricular segments during DSE, and reported, a stress-induced reduction of peak lengthening of early diastolic velocity which was accurate and superior to peak systolic tissue Doppler recordings for detecting coronary artery stenosis [37].…”
Section: Changes In Myocardial Velocities and Time Intervals During Dsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding late diastolic velocity (A), there was no significant difference between the two groups. These results are in agreement with data reported by Von Bibra et al [37] using pulsed Doppler myocardial mapping of 12 left ventricular segments during DSE, and reported, a stress-induced reduction of peak lengthening of early diastolic velocity which was accurate and superior to peak systolic tissue Doppler recordings for detecting coronary artery stenosis [37].…”
Section: Changes In Myocardial Velocities and Time Intervals During Dsupporting
confidence: 92%
“…The peak velocity response for both systole and diastole has been shown to be significantly lower during dobutamine stress in malperfused myocardial regions compared to normal [37,38].…”
Section: Changes In Myocardial Velocities and Time Intervals During Dmentioning
confidence: 96%
“…Pulsed wave tissue Doppler images were recorded on a commercially available ultrasound system (Vingmed System FiVe; GE Medical Systems, Milwaukee, WI) with a 2.5 MHz transducer. The technique of using tissue Doppler imaging has been recently described (14). In short, the Doppler sampling gate (8 mm) was consecutively placed in the basal septal, anteroseptal, anterior, lateral, posterior, and inferior wall for the assessment of longitudinal left ventricular function.…”
Section: Methodsmentioning
confidence: 99%
“…This technique has been used for the assessment of both global and regional myocardial function and is reported to be more sensitive to functional changes than traditional echocardiographic and Doppler methods (13,14).…”
mentioning
confidence: 99%
“…One study has demonstrated that dobutamine induced changes in peak Ew of the LV wall (≥2 cm/s) can be used to detect myocardial ischemia [77]. Moreover, a study of athletes has indicated that the Ew for the LV inferior wall is a useful marker of aerobic training [78].…”
Section: Figmentioning
confidence: 99%